2023
DOI: 10.3390/cells12111529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell Age and Membrane Rigidity on Red Blood Cell Shape in Capillary Flow

Mohammed Nouaman,
Alexis Darras,
Thomas John
et al.

Abstract: Blood flow in the microcirculatory system is crucially affected by intrinsic red blood cell (RBC) properties, such as their deformability. In the smallest vessels of this network, RBCs adapt their shapes to the flow conditions. Although it is known that the age of RBCs modifies their physical properties, such as increased cytosol viscosity and altered viscoelastic membrane properties, the evolution of their shape-adapting abilities during senescence remains unclear. In this study, we investigated the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 91 publications
2
6
0
Order By: Relevance
“… 25,27 Previous work revealed differences in the dynamic deformation behavior between control RBCs and artificially stiffened RBCs, as well as RBCs of diabetes patients in microcapillary flow. 15,48,49 In our study, the observed increase of cell elongation for stable croissants is in good agreement with previous investigations on single RBCs. 11,50 This is attributed to the two “tails” of the croissant-shaped RBC that seem to become longer and pointed [see the top row in Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“… 25,27 Previous work revealed differences in the dynamic deformation behavior between control RBCs and artificially stiffened RBCs, as well as RBCs of diabetes patients in microcapillary flow. 15,48,49 In our study, the observed increase of cell elongation for stable croissants is in good agreement with previous investigations on single RBCs. 11,50 This is attributed to the two “tails” of the croissant-shaped RBC that seem to become longer and pointed [see the top row in Fig.…”
Section: Resultssupporting
confidence: 93%
“…4(e) ]. Such pdfs with two pronounced peaks at elevated velocities have been reported before 15,31 and are also found in the most confined channel [ Fig. 4(a) ] due to the emergence of both off-centered slippers and central flowing croissants and other shapes.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations